Prazerosa : interactive reading chair - Gaspar, Rui (2018)
This article describes how to promote reading amongst children, changing the focus on the languages traditionally involved in the print, to the reading environment and adding other interactive languages, has led to the invention of: “Prazeroza – Interactive Reading Chair”. The intention is to generate a peculiar reading environment, an immersive one, created through interactivity. The reader already constructs in his imagination, when reading a book, to real sensations felt through his body, vary accordingly with the narrative's characteristics. This article is started by describing a possible interaction between reader and Prazerosa. After which, it will lay all the paths taken regarding aesthetics, literature, mechanics, electronics and computation, to arrive to the desired immersive reading environment. This approach combines the interactive and virtual between the reader, the visual languages present in the book, and the machinery and luminosity of languages introduced by Prazeroza.